2016
DOI: 10.1017/s1751731116000859
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation and reticuloruminal pH in periparturient dairy cows experiencing different lipolysis early postpartum

Abstract: Metabolic adaptation includes an array of concerted metabolic and endocrine events that enable dairy cows bridging the period of energy deficit at the onset of lactation. The present study evaluated metabolic, endocrine and reticuloruminal pH changes in 30 (25 Holstein and five Simmental) periparturient dairy cows experiencing variable lipolysis early postpartum. Cows were fed the same close-up and fresh lactation diets and kept in the same management conditions. Blood samples were collected at day 14, and day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The trial was conducted at the Dairy Research Facilities of the Institute of Livestock Research, Agricultural Research and Education Centre Raumberg-Gumpenstein, Austria). The experiment was part of a larger study reported elsewhere [ 10 ]. Data of metabolic adapation of cows, energy and nutrient balance, and rumen pH during transition period are presented in that article.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trial was conducted at the Dairy Research Facilities of the Institute of Livestock Research, Agricultural Research and Education Centre Raumberg-Gumpenstein, Austria). The experiment was part of a larger study reported elsewhere [ 10 ]. Data of metabolic adapation of cows, energy and nutrient balance, and rumen pH during transition period are presented in that article.…”
Section: Methodsmentioning
confidence: 99%
“…A smooth metabolic adaptation during the transition period is of utmost importance to prevent excessive mobilization of fat tissues and consequently to improve animal health and productivity. We recently observed different metabolic adaptation strategies in periparturient dairy cows to cope with the energy deficit postpartum, despite similar feeding and management conditions [ 10 ]. Although these cows had similar milk production, body weight and body condition scores, they showed different levels of circulating NEFA and differed in the estimated sensitivity to insulin.…”
Section: Introductionmentioning
confidence: 99%
“…The rumen pH was continuously measured from week 3 to week 10 after parturition using indwelled wireless pH-transmitting units (smaXtec animal care sales GmbH, Austria) as described recently (Humer et al 2016). Blood samples were collected shortly before the morning feeding from the coccygeal vein at weeks 3, 6, and 13 after parturition using 10 ml serum vacutainer tubes (Vacuette ® , Greiner BioOne GmbH, Austria).…”
Section: Animals the Trial Was Conducted At The Dairy Research Facilmentioning
confidence: 99%
“…It normally takes 6-10 weeks after parturition until cows meet their energy requirements totally through diet, although strong individual variation in the NEB level and body tissue mobilization is well known in the transition cows (Gruber et al 2014;Humer et al 2016). However, there is a paucity of information regarding the influence of the level of meeting the energy and nutrient needs on the reproductive performance in cows during early lactation.…”
mentioning
confidence: 99%
“…It appears that exposure to high levels of ammonia or urea may impair the maturation of oocytes and subsequent fertilization or maturation of developing embryos. Successful embryo development depends upon the nature of the uterine environment, while increased urea level can decrease the uterine pH that would negatively affect the implantation (2) and development of embryos, mostly at the cleavage and blastocyst formation stage (16). However, supplying adequate energy for excretion of excess ammonia or urea may prevent these negative effects on reproductive performance of cows.…”
Section: Effect Of Dietary Proteinmentioning
confidence: 99%